Implementasi Kincir Angin Savonius 2 Tingkat Menggunakan Generator Magnet Permanen - Jefri Lianda; Hikmatul Amri (Politeknik Manufaktur Negeri Bangka Belitung, 2017)
This paper focuses on improving the performance of a two-tiered windmill savonius to generate electricity through a permanent magnet generator. This study used an experimental method, taking into account the number and angle of the wind turbine Savonius two levels. The study was conducted at wind speed conditions of about 2.85 m / s to 6.42 m / s. Dimensions of windshield savonius blades with a width of 45 cm and a height of 50 cm. The wind turbine is installed with a height of 3.5 meters from the ground. This study uses a gearbox with a ratio of 1: 3.This study produces a maximum power of 95 watts. The average voltage generated 13.75 volts AC to 19.52 volts AC. The energy supplied to the battery uses a battery charger control (BCR).